If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + 27 = 9x + 36 Reorder the terms: 27 + 18x = 9x + 36 Reorder the terms: 27 + 18x = 36 + 9x Solving 27 + 18x = 36 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 27 + 18x + -9x = 36 + 9x + -9x Combine like terms: 18x + -9x = 9x 27 + 9x = 36 + 9x + -9x Combine like terms: 9x + -9x = 0 27 + 9x = 36 + 0 27 + 9x = 36 Add '-27' to each side of the equation. 27 + -27 + 9x = 36 + -27 Combine like terms: 27 + -27 = 0 0 + 9x = 36 + -27 9x = 36 + -27 Combine like terms: 36 + -27 = 9 9x = 9 Divide each side by '9'. x = 1 Simplifying x = 1
| c=200+25x | | -2/3y=10.6 | | 2*5x=10*2x | | 5a-10b-10a+6b/2a | | 8x+7=16+5x | | (5a-10b-10a+6b)/2a | | b=1/2*m*p | | -6b+8+4b=-3b+13 | | 28=2[(w+2)+w] | | 2x+240=260 | | -3a+5+4a=11-27 | | 15=7w+2/2+3w+5/4 | | 3R=D+5 | | V=9*6*5 | | (x+4)+(2x-1)=24 | | 10y=4y+10+5 | | 4z+20=3z+3 | | C=2*3.14*7.24 | | (x+15)*3/5-7/12=15 | | x+15*3/5-7/12=15 | | 1/2*23*38=A | | 1/2*23*38 | | -6x+40=31-4x | | x^2-14x=4 | | 2x+240=250 | | 169m^2=0 | | 2x+100=110 | | 33t-26=13t-6 | | 2222222222222222x-5=x-9 | | 38s+15=-2s | | 58x^2+86x+65=35 | | 22x-5=x-9 |